Outcomes of non-anaplastic stage III and 'inoperable' Wilms tumour treated in the UKW3 trial. (February 2019) - Irtan, Sabine; Messahel, Boo; Moroz, Veronica; Taylor, Roger E.; Grundy, Richard; Kelsey, Anna; Vujanic, Gordan; Pritchard-Jones, Kathy; ,
Highlights: Survival rates for Wilms tumour were similar whatever the reason to be stage III. Radiotherapy avoidance in selected stage III WT may not alter survival. Tumours deemed 'inoperable' at diagnosis do not need radiotherapy if pathological stage I/II. Abstract: Background and purpose: To describe the outcome of patients with stage III Wilms tumours (WT) treated in the UKW3 trial. Material and methods: Patients with a pathologically confirmed stage III non-anaplastic WT at nephrectomy (Group A) or with an 'inoperable' tumour at diagnosis managed by biopsy and pre-operative chemotherapy (Actinomycin D-Vincristine-Doxorubicin) but stage I or II at subsequent nephrectomy (Group B) were included. Results: The 4-year overall (OS)/event free survival (EFS) for Group A ( n = 117) patients was 90%(95%CI:83–94)/81%(CI:73–87) and for Group B ( n = 32) 94%(CI:77–98)/88%(CI:70–95). The 4-year OS/EFS of patients with pathological stage III WT according to whether they received flank/abdominal radiotherapy (95 patients) or not (37 patients, 22 from UKW3 pooled with 17 patients from UKW2) were 91%(CI:83–95)/82%(CI:73–89), and 84%(CI:67–92)/78%(CI:61–89), respectively. The 4-year OS/EFS for patients having one reason to be stage III versus two or three was 92%(CI:84–96)/83%(CI:73–90) and 85%(CI:70–93)/78%(CI:61–88), respectively. Conclusion: Our findings question the inclusion of biopsy or pre-operative chemotherapy as sole criterion for assigning a tumour stage III. Selected patients with pathological stage III WT can survive without radiotherapy. Whilst cautious interpretation is needed due to the post hoc nature of these analyses, further biological studies may better characterise those who could benefit from reduced therapy.